Role of Computer Science (Artificial Intelligence) In Poultry Management - Patel, Hrishitva; Sana, Adil (Green Publisher Indonesia, 2022)
The precise control of animals is the focus of a new strategy to enhance animal welfare in the poultry industry. We notice that good welfare circumstances significantly impact the health of the birds and the quality of the poultry products, which affects economic effectiveness in the production of poultry. An innovation that can aid farmers in more successfully controlling the environment and birds' health is using technology solutions in various animal production systems. Additionally, as public concern over chicken breeding and welfare increases, resolutions are being developed to improve control and monitoring in this area of animal agriculture. PLF (precision livestock farming) uses various techniques to gather real-time data about birds. By spotting diseases and stressful conditions in the early stages and enabling action to be taken swiftly enough to avoid the negative impacts, PLF can assist prevent reducing animal wellbeing. To enhance precision livestock farming, this review links the potential uses of the most recent technology to monitor laying hens and broilers